Regulatory rights : Supreme Court activism, the public interest, and the making of constitutional law - Yackle, Larry W. (University of Chicago Press, 2007)
We often hear?with particular frequency during recent Supreme Court nomination hearings?that justices should not create constitutional rights, but should instead enforce the rights that the Constitution enshrines. In Regulatory Rights, Larry Yackle sets out to convince readers that such arguments fundamentally misconceive both the work that justices do and the character of the American Constitution in whose name they do it. It matters who sits on the Supreme Court, he argues, precisely because justices do create individual constitutional rights. Traversing a wide range of Supreme Court decisio.